Behavioral tagging: Plausible involvement of PKMζ, Arc and role of neurotransmitter receptor systems. (November 2018) - Vishnoi, Shruti; Naseem, Mehar; Raisuddin, Sheikh; Parvez, Suhel
Highlights: Behavioral Tagging hypothesis relies on the setting of a learning tag and the synthesis of plasticity related proteins. Novelty modulates the process of behavioral tagging. Involvement of PKMζ, Arc as PRPs and neurotransmitter receptor systems in behavioral tagging. Dopamine, NMDA glutamate and β-adrenergic receptor systems play critical role in behavioral tagging. Abstract: There are many evidences in support of Behavioral Tagging hypothesis that relies on the setting of a learning tag and the synthesis of plasticity related proteins (PRPs). It explains that how a learning tag produced as a result of weak training can be paired up with PRPs that arrive as a result of novelty and consequently lead to long lasting memories. In the following review we have focused on possible involvement of PKMζ, Arc as PRPs and neurotransmitter receptor systems ACh, metabotropic glutamate in behavioral tagging along with evidences in support of involvement of dopamine, NMDA glutamate and β-adrenergic receptor systems in behavioral tagging.